Growth responses of cherry tomato plants (Solanum lycopersicum L.) under elevated temperature and different nitrogen doses - Christian, Ramot; Susila, Anas Dinurrohman; Krisantini (Journal of Agrosociology and Sustainability, 2025)
Background: Cherry tomatoes are one of the horticultural crops that can potentially be cultivated with household farming systems to fulfil the food supply. The increasing global temperature caused by climate change makes growing cherry tomato plants challenging. Besides that, nitrogen efficiency in the cultivating process of cherry tomato plants is crucial. This study aims to know the growth responses of cherry tomato plants in temperature and nitrogen doses. Methods: A completely randomized design with two factors was used for this study. The first factor was the temperature (normal and high-temperature treatment). The second factor was the nitrogen doses (55 ppm, 110 ppm, and 165 ppm). Observations of growth characteristics included plant height, leaf number, stem diameter, root length, root fresh weight, root dry weight, root-shoot ratio, shoot fresh weight, shoot dry weight, plant canopy diameter, and growth index. Findings: On day 8, normal temperature was the best result for enhancing the number of leaves. Besides that, nitrogen 55 ppm was the most effective for increasing the number of leaves. Next, at day 20, normal temperature was the best result for increasing leaf number, stem diameter, root length, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight, and growth index. Then, nitrogen 110 ppm + normal temperature was the most significant response of root-shoot ratio. Conclusion: Normal temperature and minimal nitrogen doses were the most effective conditions for enhancing the growth of cherry tomato plants.  Novelty/Originality of this article: This study examines cherry tomato plants' remarkable ability to grow at normal temperature and minimum nitrogen level.